2014
DOI: 10.1186/1479-5868-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and socio-demographic associates of children’s active transport to school: a cross-sectional investigation from the URBAN Study

Abstract: BackgroundActive transport (e.g., walking, cycling) to school (ATS) can contribute to children’s physical activity and health. The built environment is acknowledged as an important factor in understanding children’s ATS, alongside parental factors and seasonality. Inconsistencies in methodological approaches exist, and a clear understanding of factors related to ATS remains equivocal. The purpose of this study was to gain a better understanding of associates of children’s ATS, by considering the effects of dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 55 publications
(70 reference statements)
4
58
2
Order By: Relevance
“…Model 2 showed that a limited number of variables are associated with children's mode choice, confirming the results of Oliver et al (2014). Concerning children's individual characteristics, a persistent finding across the models was that age is positively related to walking and cycling, with a distinct effect for the former.…”
Section: Principal Findings Concerning the Individual Effectssupporting
confidence: 69%
See 1 more Smart Citation
“…Model 2 showed that a limited number of variables are associated with children's mode choice, confirming the results of Oliver et al (2014). Concerning children's individual characteristics, a persistent finding across the models was that age is positively related to walking and cycling, with a distinct effect for the former.…”
Section: Principal Findings Concerning the Individual Effectssupporting
confidence: 69%
“…To the best of our knowledge, it is the first comparative study of these three urban form utilizations and how they affect model interpretation. While several Anglophone studies have been published (e.g., Kerr et al, 2006;McMillan, 2007;Noland, Park, Von Hagen, & Chatman, 2014;Oliver et al, 2014;Mitra, Papaioannou, & Habib, 2016;Woldeamanuel, 2016), European studies (e.g., M€ uller et al, 2008;Broberg & Sarjala, 2015;Kaplan et al, 2016) are underrepresented (Lu et al, 2014). We focused on the Netherlands, a country that is highly attuned to walking and cycling (Pucher & Buehler, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted by Oliver et al (2014), the joint consideration of multiple built environmental variables provokes multicollinearity problems in regressions (Lu Table 1 Descriptive statistics stratified by active and passive modes on a trip level.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Data for 8 regional studies totaling 6329 participants from Auckland, Wellington, Christchurch, and Dunedin cities supplemented the calculation of this score. 15,[17][18][19][20][21][22][23] With the exception of 1 study, all assessed multiple measures of screen time. Across these studies, an average of 49% of children and youth met the recommendation of watching less than 2 hours of screen time daily, with a range of 17% to 96%.…”
Section: Overall Physical Activity: B-mentioning
confidence: 99%
“…Data were derived from 8 studies, 15,[17][18][19][20][21][22][23] in total comprising 3363 sociodemographically diverse children and youth from Auckland, Wellington, Christchurch, and Dunedin cities. On average, 54% of children in these studies participated in at least 60 minutes of MVPA per day.…”
Section: Overall Physical Activity: B-mentioning
confidence: 99%